UPAYA MENINGKATKAN HASIL BELAJAR PKN MATERI LEMBAGA LEMBAGA NEGARA MELALUI METODE EXPLICIT INTRUCTIONS PADA SISWA KELAS VIA SD NEGERI 01 SURUH TASIKMADU KABUPATEN KARANGANYAR SEMESTER II TAHUN PELAJARAN 2014/2015 - Widyastuti, Sri (Widya Wacana: Jurnal Ilmiah, 2016)
The problem of this research is “Can explicit instruction method improve the study result of CivicEducation about state institution of the sixth grade students in SDN 01 Suruh Tasikmadu Karanganyaremester II in the academic year fo 2014/2015.The purpose of this research is to improve the study result of Civic Education about stateinstitution of the sixth grade students in SDN 01 Suruh Tasikmadu Karanganyar semester II in theacademic year of 2014/2015.This research is Classroom Action Research with the subject of the sixth grade students in SDN 01Suruh Tasikmadu Karanganyar semester II in the academic year of 2014/2015. This grade consists of 23students. This classroom action reaserach was carried out for 3 months, from February until April 2015 in3 cycles. The data collecting method used is tes. Meanwhile, the data analysis in this research isqualitative descriptive technique of every cycle.From the data analysis can be concluded that the study result of Civic education about stateinstitution through explicit instruction method significantly improve.In the pre research, the average score is 67, while in cycle II is 74. Then, in cycle III is 82.Therefore, Using Explicit Instruction Method can improve the study result of Civic Education about stateinstitution of the sixth grade students in SDN 01 Suruh Tasikmadu Karanganyar emester II in theacademic year fo 2014/2015. In can be seen from the score at before an after the action.Key Words: Study Result, Explicit Instruction, Civic Education